Causes of the (current) high inflation rates in the Czech Republic and the United States - Slaninka, Šimon; Šíma, Ondřej; Koderová, Jitka; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
There is an ongoing debate about causes of high inflation in post-covid economy. As to solve the problem of high inflation, it is crucial to understand what the root causes are to be able to address them most efficiently. This thesis examines the causes of inflation, with a particular focus on the Keynesian approach, which finds causes in real economy. The research is based on literature review of existing publications on inflation and on an analysis of empirical data from the Czech Republic and the US. The findings shows that inflation in the Czech Republic was mainly caused by released demand after pandemic, expansionary fiscal policy on demand-pull side and by increased energy and agricultural commodities due to war in Ukraine and rising wages on cost-push side. Followingly, the main culprits of inflation in the US were expansionary fiscal policy and higher cost of fuel that was soon after reflected in prices of other goods and services.
Vedoucí práce: Ondřej Šíma
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses